High and Low Task Stimulation Jobs: A Causal Analysis of Performance-Satisfaction Relationships - Ivancevich, John M. (Academy of Management Journal, 1979)
This study of project engineers investigated the direction and causal influence of a number of performance- satisfaction relationships. For the high task stimulation jobs, it was found that high intrinsic satisfaction caused decreases in subsequent supervisory performance rating and cost performance. For the low task stimulation jobs, extrinsic satisfaction was inferred to be the cause of increased supervisory ratings and cost performance.